Identification and Expression Analysis of an Interacting Protein (LvFABP) that Mediates Vibrio parahaemolyticus AHPND Toxin Action - Gu, Xiaoqian; Liu, Mei; Wang, Baojie; Jiang, Keyong; Wang, Lei (Frontiers in Immunology, 2022)
Acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus causing AHPND (VPAHPND) is the most serious disease affecting shrimp farming. The PirAvp and PirBvp toxins of VPAHPND are known virulence factors. However, the corresponding target protein in shrimp that mediates their action has not been identified. By screening yeast two-hybrid cDNA libraries from intestine, stomach, and hepatopancreas of Litopenaeus vannamei, the protein with the largest increase in gene expression in shrimp hepatopancreas in response to VPAHPND challenge was identified and designated LvFABP. Analysis revealed high sequence homology of the LvFABP gene and a lipocalin/cytosolic fatty acid binding gene. Yeast two-hybrid pairwise analysis, GST-pull down assay, and far-western blot assay were performed to determine the interaction between LvFABP and PirBvp. LvFABP was able to directly bind to PirBvp. The expression of LvFABP in the hepatopancreas was significantly higher at P23 and P27 developmental stages of L. vannamei. RNA interference (RNAi) of LvFABP reduced the mortality, histopathological signs of AHPND in the hepatopancreas, and the number of virulent VPAHPND bacteria in the intestine, stomach, and hepatopancreas after VPAHPND challenge. We concluded that the LvFABP was involved in AHPND pathogenesis and acted as a VPAHPND toxin interacting protein. This is the first identification of VPAHPND toxin interacting protein from the shrimp digestive system by yeast two-hybrid library screening and were confirmed by in vitro protein interaction verification and in vivo challenge experiments. This study provides novel insight into the contributions of LvFABP towards AHPND pathogenesis in shrimp. The findings could inform AHPND preventative measures in shrimp farming.